De novo annotation reveals transcriptomic complexity across the hexaploid wheat pan-genome - White, Benjamen; Lux, Thomas; Rusholme-Pilcher, Bachel; Juhász, Angéla; Kaithakottil, Gemy; Duncan, Susan; Simmonds, James; Rees, Hannah; Wright, Jonathan; Colmer, Joshua; Ward, Sabrina; Joynson, Ryan; et al. (Nature Publishing Group, 2025)
Wheat is the most widely cultivated crop in the world, with over 215 million hectares grown annually. The 10+ Wheat Genomes Project recently sequenced and assembled to chromosome-level the genomes of nine wheat cultivars, uncovering genetic diversity and selection within the pan-genome of wheat. Here, we provide a wheat pan-transcriptome with de novo annotation and differential expression analysis for these wheat cultivars across multiple tissues. Using the de novo annotations we identify cultivar-specific genes and define the core and dispensable genomes. Expression analysis across cultivars and tissues reveals conservation in expression between a large core set of homeologous genes, in addition to widespread changes in subgenome homeolog expression bias between cultivars and cultivar-specific expression profiles. We utilise both the newly constructed gene-based wheat pan-genome and pan-transcriptome, demonstrating variation in the prolamin superfamily and immune-reactive proteins across cultivars.